2014
DOI: 10.1590/1678-41626204
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da carne de suínos com uso de glicerina na alimentação

Abstract: Universidade Federal de Lavras  Lavras, MG  RESUMO O objetivo deste trabalho foi avaliar os efeitos do fornecimento de diferentes níveis de glicerina na alimentação sobre a qualidade da carne de suínos em terminação. Foram utilizados 30 machos castrados e 30 fêmeas que apresentaram peso inicial de 79,3±4,0kg. Utilizou-se delineamento em blocos casualizados (peso inicial) em esquema fatorial 2 × 4 + 2, sendo duas categorias sexuais (macho castrado e fêmea), quatro níveis de glicerina bruta (50, 100, 150 e 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
3
4
0
1
Order By: Relevance
“…Our results regarding the carcass characteristics are in accordance to those reported by other authors (Mendoza et al, 2010;Egea et al, 2016) for backfat thickness, since the energy value of glycerin is similar to that of corn (Melo et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results regarding the carcass characteristics are in accordance to those reported by other authors (Mendoza et al, 2010;Egea et al, 2016) for backfat thickness, since the energy value of glycerin is similar to that of corn (Melo et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…All diets were isonutritive and isocaloric. Crude glycerin was included as substitution for corn, considering its metabolizable energy value of 3,475 kcal/kg (Melo et al, 2014). The ractopamine was added to the mix in substitution to kaolin.…”
Section: Animals Experimental Design Diet and Feedingmentioning
confidence: 99%
“…In the same way, Della Casa et al (2009) did not find differences in carcass characteristics with addition of semi-purified glycerin at the levels of 0, 5, and 10%. Melo et al (2014) evaluated glycerin as an ingredient of finishing pig diets and found a significant difference for the red content, but because there was no difference in any other variables, the authors recommended the use of glycerin up to the level of 20% without influencing the meat and carcass characteristics of swine.…”
Section: Resultsmentioning
confidence: 99%
“…are increasingly concerned about the nutritional value of meat, in view of recommendations to reduce intakes of saturated fatty acids to avoid the occurrence of heart disease (jAKobSen et al, 2009;MArçAL et al, 2016). In this way, it is possible to manipulate the meat quality according to the type and quantity of feed provided (MeLo et al, 2014).…”
Section: Consumersmentioning
confidence: 99%